Strategi Koperasi Karya Mandiri Dalam Memperkenalkan Product Knowledge Melalui Event Gowes Pesona Nusantara - Erik Maudi; Susilowati Susilowati (Universitas Bina Sarana Informatika, 2018)
Cooperative function amid the current society it is necessary as a support to the economy of certain community groups in order to build and develop the economic potential of the community. Koperasi Karya Mandiri following the participation of the event